The arresting gaze: Artistic disruptions of antiblack surveillance. (July 2020) - Monahan, Torin
This article analyzes a range of art and performance pieces that unearth and problematize the racist cultural underpinnings of surveillance. Drawing upon recent black studies scholarship, I probe the ways that contemporary creative works disrupt dominant signifying regimes that would position racialized surveillance/violence couplings as historical and exceptional rather than as foundational and routine. I argue that such aesthetic disruptions achieve creative vitality by holding in tension exclusionary regimes of white liberal personhood, on one hand, and articulations of hope that depart from those regimes, on the other. Whereas the gaze of surveillance seeks to silence and arrest subjects, creative expression can undermine authorized forms of visuality by focusing on survival and community that persist in spite of it.